ANALISIS YURIDIS MENGENAI PENGATURAN HUKUM HAK CIPTA PADA PRODUK DIGITAL DALAM BISNIS KREATIF - Widiadnyan, I Gusti Ayu; Dewi Yani Putri, Ni Luh Ketut (Universitas Mahendradatta, 2025)
Copyright has an important role in protecting intellectual works, especially in the rapidly developing digital era. This research aims to analyze legal regulations regarding copyright protection on digital products in creative businesses, as well as legal efforts that can be taken to protect copyright on digital products in creative businesses. The research method used is a normative juridical approach by analyzing statutory regulations, legal doctrine, and case studies related to copyright infringement in the digital realm. The research results show that copyright regulations in Indonesia are regulated in Law Number 28 of 2014 concerning Copyright, which includes protection for digital products such as works of art, music, graphic design and applications. However, challenges such as lack of legal awareness, minimal law enforcement, and technological advances that enable illegal distribution are still major obstacles. For this reason, synergy is needed between the government, business actors and the public in increasing understanding, supervision and law enforcement of copyright in the digital sector. This research provides recommendations in the form of increasing supervision through digital systems, and public education as strategic steps in protecting digital product copyrights in creative businesses. Thus, adequate legal protection can encourage the growth of creative industries that are sustainable and competitive.